Evolution: the paradox of sperm leviathans. - Pizzari, T (2006)
Sexual selection theory predicts that sperm competition will push males to produce more, smaller sperm. Paradoxically, in the fruitfly Drosophila bifurca sperm competition is rife but males produce few, giant sperm--the largest known. A recent study reconciles the evolution of giant sperm with theory.